2018
DOI: 10.1186/s12933-018-0694-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of change in fasting glucose on the risk of myocardial infarction, stroke, and all-cause mortality: a nationwide cohort study

Abstract: BackgroundThe effect of change in blood glucose levels on the risk of cardiovascular disease among individuals without diabetes is currently unclear. We aimed to examine the association of change in fasting serum glucose with incident cardiovascular disease and all-cause mortality among representative large population.MethodsWe analyzed the data from retrospective cohort of Korean National Health Insurance Service. In total, 260,487 Korean adults aged over 40 years, without diabetes mellitus and cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
44
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 37 publications
7
44
1
5
Order By: Relevance
“…Consistent with our study, several previous studies have demonstrated the J-shaped relationship between fasting glucose level and adverse outcomes, including all-cause mortality and CV events, not only in people with diabetes but also in the healthy population [12][13][14][15]. Recent meta-analyses and a nationwide observational study revealed an increased risk of CV event in adults with prediabetes even in fasting glucose range (100-125 mg/dL) [16,17]. On the contrary, our study showed that the fasting glucose range of 95-124 mg/dL seemed to be optimal for the prevention of CV events in patients with diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our study, several previous studies have demonstrated the J-shaped relationship between fasting glucose level and adverse outcomes, including all-cause mortality and CV events, not only in people with diabetes but also in the healthy population [12][13][14][15]. Recent meta-analyses and a nationwide observational study revealed an increased risk of CV event in adults with prediabetes even in fasting glucose range (100-125 mg/dL) [16,17]. On the contrary, our study showed that the fasting glucose range of 95-124 mg/dL seemed to be optimal for the prevention of CV events in patients with diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…Our results regarding the association between incident IFG and risk of CVD, were in line with those of a Korean population [11] showing no higher hazard for CVD. Moreover, in our study we found an unexpected finding regarding those with NFG/NGT who converted to IFG/ IGT that showed 28% lower risk of CVD.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the results were on the basis of a "snapshot" measurement of blood glucose, and the authors did not consider isolated IFG and IGT groups. A few studies with varying estimates of the CVD risk have assessed the impact of IFG/IGT with or without conversion to diabetes [8][9][10][11]; however, it's difficult to compare the results due to the different sample size, age Table 2 HRs (95% (CI) of CVD and CHD for subjects with incident IR and those with changing IR status between baseline and the first follow-up (n = 803) Incident IR, those who converted from IS state to IR state. IR and IS among men was defined as HOMA-IR ≥ 2.17 µU/mL and < 2.17 µU/mL, respectively; corresponding values form women were ≥ 1.85 µU/mL and < 1.85 µU/mL respectively [23] IR, insulin resistance; IS, insulin sensitive; HR, hazard ratios; CI, confidence interval; CVD, cardiovascular disease; CHD, coronary heart disease a Model 1: Age, sex of participants, duration of changes in glucose category states and type and number of confounders [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-life observations performed in large cohorts of T2D individuals indicate a variable mortality rate, higher in the Western countries [15][16][17] and lower in Arab countries [18], and declining over the last decade [19]; diabetes duration is, indeed, one of the main determinants of such risk [20,21]. In our small sample we show that, despite the intensive treatment of all risk factors and comorbidities, the mortality rate of the patients over the rst ve years of known disease is superimposable to that of patients with much higher diabetes duration and prevalence of comorbidities, con rming the relative weight of prediabetes state in determining a higher CV and, of less extent, mortality risk [10,22,23]. Another possibility could be a short-term negative effect on mortality that follows the diagnosis of diabetes in older adults; such phenomenon was not reported in the large subset of the Kaiser Permanente Northern California with the same age of our patients and a short diabetes duration, where the mortality rate was 19.61/1000 patients/year [24].…”
Section: Discussionmentioning
confidence: 55%